2020
DOI: 10.1111/nyas.14436
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of neurogenesis and melatonin regulation in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is an age-related neurodegenerative disorder characterized by the hallmark pathologies of amyloid-beta plaques and neurofibrillary tangles. Symptoms of this devastating disease include behavioral changes and deterioration of higher cognitive functions. Impairment of neurogenesis has also been shown to occur in AD, which adversely impacts new neuronal cell growth, differentiation, and survival. This impairment possibly results from the cumulative effects of the various pathologies of AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 130 publications
(318 reference statements)
0
24
0
2
Order By: Relevance
“…The factors influencing the experience- and exercise-dependent stimulation of neurogenesis have been intensively pursued given the potential to harness this knowledge for therapeutic benefit in conditions associated with cognitive decline such as Alzheimer’s disease ( Chohan, 2020 , Mihardja et al, 2020 ). One potential approach is to develop exercise- or environment-mimetic drugs that activate the pathways recruited by enrichment for clinical benefits in patients ( Guerrieri et al, 2017 , Shepherd et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The factors influencing the experience- and exercise-dependent stimulation of neurogenesis have been intensively pursued given the potential to harness this knowledge for therapeutic benefit in conditions associated with cognitive decline such as Alzheimer’s disease ( Chohan, 2020 , Mihardja et al, 2020 ). One potential approach is to develop exercise- or environment-mimetic drugs that activate the pathways recruited by enrichment for clinical benefits in patients ( Guerrieri et al, 2017 , Shepherd et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a postmortem study, it was recently demonstrated that AD patients had decreased neurogenesis and neuronal differentiation levels in contrast to healthy subjects; this fact was inferred from doublecortin staining in the dentate gyrus of the hippocampus [2]. Importantly, melatonin can increase neurogenesis [72,76], the immature neurons survival [77], and dendrites complexity [39] in animal models, suggesting that the administration of this indoleamine to AD patients may help stimulate neuronal production, survival, and elongation of their neurites, needed to form synaptic contacts and preserve circuitry integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, if melatonin can scavenge free radicals to mitigate oxidative stress avoiding neuronal apoptosis and simultaneously preserve the integrity of the dendritic arbors, and also improves sleep-wake patterns [83,84], then aged population with reduced circulating levels of this indoleamine and sleep disorders might have increased vulnerability to suffer neurodegeneration after even a moderate pro-oxidant event. Furthermore, since melatonin induces neurogenesis, promotes survival of new neurons in the hippocampus [53,72,76,77], modulates overall neuroplasticity [75], and regulates main functions such as metabolism or sleep, low melatonin levels and/or a misalignment of its biosynthesis due to circadian disruption [72], could be an additional mechanism underlying impaired brain functioning and impoverishment of quality of life in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Restoring rhythmicity via chronotherapy may ameliorate the symptoms of myriad neurological disorders that involve aberrant adult neurogenesis (Albrecht, 2017; Leung et al., 2020; McClung, 2013; Schnell, Albrecht, et al., 2014). In this regard, the circadian hormone melatonin appears to be a very promising therapeutic candidate for depression, Alzheimer's disease, neurodegenerative diseases and CNS injuries (Leung et al., 2020; Mihardja et al., 2020; Song, 2019; Valdes‐Tovar et al., 2018). In vitro, melatonin promoted survival of new neurons derived from hippocampal NSPCs, and increased survival of NSCPs and post‐mitotic immature neurons, which may explain its antidepressant effects in the Porsolt swim test (Ramirez‐Rodriguez et al., 2009).…”
Section: Circadian Control Of Stem Cell Behaviourmentioning
confidence: 99%